The effects of low hurdle and ladder training on anaerobic power and agility in women soccer players of the Thai national team - Jurarakpong, P.; Kamutsri, T.; Treeraij, A. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The purpose of this study was to investigate the effects of low hurdle and ladder training on Anaerobic Power and Agility in Women Soccer Players of Thai National Team. Nineteen female soccer players of the Thai national team (18.58+/- 1.39 years old) were participated in this study wingate and agility test were use to evaluate anaerobic power and agility of players. Three periods of training were studied: pre-training, 2 and 4 months after training. Low hurdle and ladder training 2 times per week for 4 months were added to regular soccer training program. Statistical analysis was performed using SPSS program and the difference among training periods were compared using ANOVA (repeated measurement). The result of anaerobic power during pre-training, 2 and 4 months after-training were 9.18, 10.21 and 10.66 watts/body weight, respectively. Statistical significant differences were observed between pertraining and 2 months after training as week as pre-training and 4 months after training. Agility performances during, 2 and 4 months after training were 11.60, 11.63 and 11.34 seconds, respectively 4 months after training were significant improved anaerobic power greater than those of per training 2 months after training. For agility performance, it was significant differences between per training and 4 months after training; and 2 months after training and 4 months after training. The higher anaerobic power values of 4 months after training comparing to those per-and 2 months training indicate an improved performance of power and agility in women soccer players. It can be concluded form this study that low hurdle and ladder training effectively improve anaerobic power and agility in women soccer players. Therefore, this program is suitable and beneficial for increasing performance of movement in soccer players which required explosive power and agility.